The Museum-school Mentoring Model and Personalization of Education - Kisovar-Ivanda, Tamara (Revija za elementarno izobraževanje, 2022)
Museums are certainly a potential source of excellent mentors for students at all levels of education. It is realistic to expect that a model of personalized learning with a complex system of mentoring, would yield positive results. The article deals with the attitudes of teachers, museum educators and curators on forms of mentoring in the process of personalizing education at the primary level in Croatian schools. Qualitative methodology (semi-structured interviews) was used in the research. The results of the study indicate positive attitudes of teachers and museum educators/curators towards joint mentoring through networks across educational and cultural community institutions.